2022
DOI: 10.35877/454ri.daengku1066
|View full text |Cite
|
Sign up to set email alerts
|

Religion, Customs, and Village Government in Collaborating the Pillars of Rural Development

Abstract: This research is entitled Collaborative Pillars of Rural Development, which is located in Latdalam Village, South Tanimbar District, Tanimbar Islands Regency, Maluku Province. With a qualitative descriptive model, researchers took field data to obtain scientific facts related to How Collaborative Pillars Drive Latdalam Village Development. And the results of this study are (1) the communication of the driving pillars of village development in the village of Latdalam (Village Government, Churches, and Customary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Anything that is received as compensation, whether it be material or intangible, must be quantified and provided to the recipient, who is typically the recipient of an item that is exempt from income tax (Wahab et al, 2022). Because it encompasses the criteria for eligibility, logic, rationality, and accountability as well as emotional considerations from the worker perspective, compensation is a complicated and challenging topic (Luturmas, 2022). The goal of compensation is to stimulate and motivate employees to improve work performance and increase the effectiveness and efficiency of production (Siagian, 1995).…”
Section: The Analysis Of Role Of Motivation Career Development and Co...mentioning
confidence: 99%
“…Anything that is received as compensation, whether it be material or intangible, must be quantified and provided to the recipient, who is typically the recipient of an item that is exempt from income tax (Wahab et al, 2022). Because it encompasses the criteria for eligibility, logic, rationality, and accountability as well as emotional considerations from the worker perspective, compensation is a complicated and challenging topic (Luturmas, 2022). The goal of compensation is to stimulate and motivate employees to improve work performance and increase the effectiveness and efficiency of production (Siagian, 1995).…”
Section: The Analysis Of Role Of Motivation Career Development and Co...mentioning
confidence: 99%
“…Collaboration is a broad phrase that frequently refers to a network of cooperative relationships including more than one partner [23]. Collaboration is a partnership between companies that participate and mutually agree to work together to achieve goals, share information, resources, and rewards, and make joint decisions to solve challenges [24].…”
Section: Collaborationmentioning
confidence: 99%
“…The practice of developing and exchanging bank products or services with the goal of satisfying client needs and wants is known as "bank marketing." Islamic banking growth increases every year, as can be seen from 2015-2022 had 5 units of banks and 581 units of offices. The Sharia Business Unit (UUS) has 27 units of banks and 241 units of offices.…”
Section: Introductionmentioning
confidence: 99%
“…An earlier study found that brand image is a collection of brand connections that customers build and retain in their brains. Customers who are used to using certain brands have a tendency to consistently represent such brands (Luturmas, 2022).…”
Section: Introductionmentioning
confidence: 99%